2010
DOI: 10.1073/pnas.1004571107
|View full text |Cite
|
Sign up to set email alerts
|

Signaling by olfactory receptor neurons near threshold

Abstract: An important contributing factor for the high sensitivity of sensory systems is the exquisite sensitivity of the sensory receptor cells. We report here the signaling threshold of the olfactory receptor neuron (ORN). We first obtained a best estimate of the size of the physiological electrical response successfully triggered by a single odorantbinding event on a frog ORN, which was ∼0.034 pA and had an associated transduction domain spanning only a tiny fraction of the length of an ORN cilium. We also estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 37 publications
6
52
0
Order By: Relevance
“…These odor concentrations are well within the range (1 nM-1 mM) of those used in previous studies (Bozza and Kauer, 1998;Bhandawat et al, 2005Bhandawat et al, , 2010 on dissociated OSNs. The stimuli baths applied were carefully and slowly delivered via an application pipette positioned far away (ϳ3 mm) from the cell to obtain a homogeneous distribution of the stimulus in the bath, capable of stimulating the entire cells and not a specific compartment.…”
Section: Stimuli On Osn In Vitrosupporting
confidence: 49%
See 1 more Smart Citation
“…These odor concentrations are well within the range (1 nM-1 mM) of those used in previous studies (Bozza and Kauer, 1998;Bhandawat et al, 2005Bhandawat et al, , 2010 on dissociated OSNs. The stimuli baths applied were carefully and slowly delivered via an application pipette positioned far away (ϳ3 mm) from the cell to obtain a homogeneous distribution of the stimulus in the bath, capable of stimulating the entire cells and not a specific compartment.…”
Section: Stimuli On Osn In Vitrosupporting
confidence: 49%
“…1 E), as observed in previous studies (Bozza and Kauer, 1998;Bozza et al, 2002). At all concentrations tested (1, 50, and 200 M), well within the range (1 nM-1 mM) of those used in previous experiments on isolated OSNs (Bozza and Kauer, 1998;Bhandawat et al, 2005Bhandawat et al, , 2010, odors elicited Ca 2ϩ responses ( Fig. 1) indistinguishable from those obtained in freshly plated neurons.…”
Section: Physiological Health Status Of Isolated Osnsmentioning
confidence: 79%
“…The dose-response relationship was approximately linear at its foot (Fig. 1D, Left, Inset) but was supralinear overall (Hill coefficient, 1.7 for this cell), broadly similar to the behavior of vertebrate OSNs (27,28). As expected from OSNs expressing different Ors, the sensitivity to butyl acetate varied widely across randomly recorded Or-expressing OSNs, with a half-saturating concentration of 0.6-17 mM (10 cells; 3.7 mM in Fig.…”
Section: Patch-clamp Recordings Of Odor Responses In Or-expressing Osnsmentioning
confidence: 90%
“…In the case of unitary responses that are triggered by individual odorant-binding events, spatially and functionally segregated ciliary transduction domains have been described (Bhandawat et al, 2005;Bhandawat et al, 2010). Additionally, recordings of Ca 2+ changes in individual cilia using fluorescent Ca 2+ indicator dyes have shown that Ca 2+ microdomains exist, which contain one to three CNG channels (Castillo et al, 2010).…”
Section: Introductionmentioning
confidence: 99%